Pengaruh Kualitas Produk dan Marketing Mix Terhadap Keputusan Pembelian Baju Second Impor (Thrift) pada Missmi Shop di Kota Palangka Raya - Adi Kusuma Werdana; Meitiana Meitiana; Gema Borneo Poetra; Ina Karuehni (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the influence of product quality and marketing mix on purchasing decisions. Quantitative methods are used with data collection techniques through distributing questionnaires using Google Forms. Data analysis techniques use SPSS. The results of the study indicate that 1. Product Quality (X1) is proven to have a positive and significant influence on Purchasing Decisions (Y). 2. Marketing Mix (X2) also has a positive and significant influence on Purchasing Decisions (Y). 3. Simultaneously, Product Quality (X1) and Marketing Mix (X2) have a significant influence on Purchasing Decisions (Y).